PERBANDINGAN EFEK BAP DAN KINETIN TERHADAP LAJU MULTIPLIKASI STROBERI KULTIVAR SWEET CHARLIE - Camelia Andriani; Muhamad Kadapi; Erni Suminar; Anne Nuraini (Jurnal Agroteknologi, 2023)
Seed propagation of strawberry by in vitro culture is needed to obtain high quality seeds of strawberry in large quantities. In in vitro culture, a large number of shoots is expected can be produced at the multiplication stage. Cytokinins type of PGR can be added to culture media to produce a large number of shoot. The focus of this research was to compare the effect of BAP and Kinetin affected Sweet Charlie strawberry multiplication. The experiment was located at the Seed Technology Tissue Culture Laboratory, Faculty of Agriculture, Padjadjaran University. The experimental design was a Completely Randomized Design (CRD) with two treatments of different types of cytokinin, namely Benzyl Amino Purine (BAP) and Kinetin at 1 mg L-1 on Murashige and Skoog (MS) basic media, each treatment was repeated four times. This study showed that BAP had a better effect than Kinetin on the number of shoots, number of leaves, and wet weight of strawberry Sweet Charlie cultivar. The addition of BAP was recommended over Kinetin to obtain the highest number of shoots, the highest number of leaves, and the highest wet weight of culture on strawberry Sweet Charlie cultivar.